182k views
6 votes
−5x + y = −2 −3x + 6y = −12 solved by substitution please work so i can understand

2 Answers

12 votes

Answer:

x=0 and y= -2

Explanation:

−5x+y=−2for y:

−5x+y=−2

−5x+y+5x=−2+5x(Add 5x to both sides)

y=5x−2

5x−2foryin−3x+6y=−12:

−3x+6y=−12

−3x+6(5x−2)=−12

27x−12=−12(Simplify both sides of the equation)

27x−12+12=−12+12(Add 12 to both sides)

27x=0

x=0

Substitute0 for X in y=5x−2:

y=5x−2

y=(5)(0)−2

y=−2(Simplify both sides of the equation)

User SuRu
by
5.8k points
6 votes
Make y subject:
y = -2 + 5x
Sub into other equation as y:
-3x + 6(-2 + 5x) = -12
-3x -12 + 30x = -12
27x = 0
x = 0
Sub in X to find Y:
-5(0) + y = -2
y = -2
User Kaldoran
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.